Review of Phytochemicals and Its Biological Activities and Contemporary Nutraceuticals - Laode Rijai (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
Nutraceutical is food for health with functions of preventive, promotive, rehabilitation, aesthetic, intelligence to curative. Nutraceuticals as food products can have a contemporary value, which is a trend or extraordinary circumstance that attracts consumers because of its function as a supplement, functional food, medical food, and genetically engineered food so that it penetrates the world market without limits. Nutraceuticals that are contemporary make it easy to achieve the goals of health care by using the